Ethno‐racial differences in the frequency of cancer reported from family pedigrees in the prenatal genetic counseling setting. - Palacios, Alex; Flodman, Pamela; Steinhaus French, Kathryn; Smith, Moyra; Quintero‐Rivera, Fabiola (Journal of Genetic Counseling, 2025)
This study analyzed whether differences in cancer reporting exist between different ethno‐racial groups in pedigrees from a prenatal genetic counseling setting. Data were collected from 446 charts at University of California, Irvine from January 1, 2015 to August 31, 2020. A total of 795 pedigrees meeting inclusion criteria were analyzed from four ethno‐racial groups: White, Hispanic/Latinx, Asian, and African American/Black. The total number of first‐ and second‐degree relatives affected with cancer was analyzed using contingency tables, nonparametric tests, and Poisson regression. Cancer reporting in first‐ and second‐degree relatives was highest among the White group and lower in the Latinx, Asian, and Black groups. Ethno‐racial group, presence or absence of the prospective father, and medical interpreter use were significant factors in predicting the number of relatives reported to have cancer in a Poisson regression model. Controlling for the total number of relatives in the pedigree, cancer reporting rates for the Latinx, Black, and Asian groups were 36.3%, 50.2%, and 65.5%, respectively, of that in the White pedigrees. Cancer reporting rates observed in Asian pedigrees (in comparison to White pedigrees) were similar to the rates reported by the Centers for Disease Control and Prevention, but reporting in the Latinx and Black pedigrees was less than would be expected based on population incidence. This suggests that cancer histories in some people of color (POC) may be truncated. Healthcare professionals should recognize that certain patient populations may have limited knowledge of their family cancer history, or that such information may not be disclosed due to nuances of cultural differences or possible provider bias. In order to provide appropriate risk assessment, interventions addressing structural barriers should be undertaken in prenatal clinics to reduce existing health disparities and improve health outcomes in POC, since this may be the only opportunity to obtain a comprehensive family health history.